Chapter Electrochemical phosphate detection in oligotrophic seawater with a stand-alone plastic electrode - Figueredo, Federico (Proceedings e report, 2020)
The northern Adriatic Sea is a particular water system, in which the levels of nutrients are commonly low or unbalanced. In general, phosphate detection can be done with the classical molybdenum-blue method. However, the method cannot be used in oligotrophic seawater samples due to its low sensitivity and high interference problems. In this study, we present a new electrochemical method, based on the application of a plastic conductive electrode containing a molybdenum reagent embedded. The sensitivity for phosphate was high enough to detect this nutrient in oligotrophic seawater.